Efek Mediasi Efikasi Diri Komputer pada Pengaruh Daya Dukung Sekolah terhadap Kompetensi Teknologi, Pedagogi, dan Konten Guru Ekonomi - Rajip Sidik; Hari Mulyadi; Sumartini Sumartini (Universitas Indraprasta PGRI Jakarta, 2022)
The purpose of this study is to determine and to analyze the effect of school support on computer selfefficacy, the effect of computer self-efficacy on technological pedagogical and content knowledge and the effect of school support on technological pedagogical and content knowledge mediated by computer self-efficacy. The research method used was an explanatory survey and the data was collected through a questionnaire. Economics teachers at the Karawang Regency Senior High School in 2021 totaling 68 teachers were determined as the population and the saturated sample was used as sampling technique by taking the entire population. Data were analyzed using descriptive statistics and mediation regression analysis. The results showed that the school support had an effect on computer self-efficacy with low contributions, computer self-efficacy had an effect on technological pedagogical and content knowledge of teachers with low contributions and school support had an effect on technological pedagogical and content knowledge of teachers with low contributions through computer self-efficacy. The results of the study have implications that in the future research on technological pedagogical and content knowledge will focus on the study of developing learning systems based on the use of ICT.